2015
DOI: 10.1111/1365-2435.12528
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation and the niche: implications for coexistence, range shifts and ecosystem functioning

Abstract: Summary 1.Viewing facilitation through the lens of the niche concept is one way to unify conceptual and empirical advances about the role of facilitation in community ecology. 2. We clarify conceptually and through examples from marine and terrestrial environments how facilitation can expand species' niches and consider how these interactions can be scaled up to understand the importance of facilitation in setting a species' geographic range. We then integrate the niche-broadening influence of facilitation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
183
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(207 citation statements)
references
References 80 publications
6
183
2
1
Order By: Relevance
“…Compared to no association, mutualism can expand a population's niche along other axes (Bruno et al 2003, Poisot et al 2011, Bulleri et al 2016, such as when endophytes increase host drought tolerance (Afkhami et al 2014b). Compared to no association, mutualism can expand a population's niche along other axes (Bruno et al 2003, Poisot et al 2011, Bulleri et al 2016, such as when endophytes increase host drought tolerance (Afkhami et al 2014b).…”
Section: Overcoming Constraints Along Other Niche Axesmentioning
confidence: 99%
“…Compared to no association, mutualism can expand a population's niche along other axes (Bruno et al 2003, Poisot et al 2011, Bulleri et al 2016, such as when endophytes increase host drought tolerance (Afkhami et al 2014b). Compared to no association, mutualism can expand a population's niche along other axes (Bruno et al 2003, Poisot et al 2011, Bulleri et al 2016, such as when endophytes increase host drought tolerance (Afkhami et al 2014b).…”
Section: Overcoming Constraints Along Other Niche Axesmentioning
confidence: 99%
“…However, a few theoretical studies also include facilitative interactions [13][14][15][16]. These models predict that, under some conditions, facilitation can maintain species-rich communities.…”
Section: Plant Species Coexistence: Insight From Theorymentioning
confidence: 99%
“…It has been found that Chironomidae often display commensalistic interactions to increase their feeding opportunity, mobility, protection from disturbance and reduce predation risk (Tokeshi, 1993;Callisto et al, 2006), but this entails interactions with other orders of aquatic invertebrates. Within-class commensalism has not been found or described for many aquatic invertebrates, yet could have a large explanatory value when it comes to niche expansion and range shifts (Bulleri et al, 2016).…”
Section: Neutral and Negative Effects Of Biotic Interactionsmentioning
confidence: 99%
“…The positive effect of an interaction, also known as facilitation, is seen as a key mechanism in which species diversity positively affects ecosystem processes and functioning (Mulder et al, 2001;Stachowicz & Byrnes, 2006;Bulleri et al, 2016). A study by Cardinale et al (2002) showed that multiple species from the same functional feeding guild (aquatic suspension-feeders) enhanced each other's feeding success by decelerating the flow from upstream to downstream neighbours.…”
Section: Introductionmentioning
confidence: 99%